Reproductive gerrymandering, bureaucratic violence, and the erosion of abortion access in the United States. - Basmajian, Alyssa L. (Medical Anthropology Quarterly, 2024)
In the contemporary American political landscape, gerrymandering and the passage of anti‐abortion legislation are intimately connected in what I call reproductive gerrymandering. I develop this concept as an analytic tool to understand the disjuncture between the passage of laws restricting reproductive healthcare access and the will of the majority of voters. In this ethnographic project, Ohio serves as an important case study where efforts to elect a supermajority of extremist anti‐abortion Republican officials has allowed for the passage of unpopular legislation restricting abortion. I argue that the mundane bureaucratic processes involved in electoral redistricting and state budget procedures are forms of bureaucratic violence that result in structural harm experienced by pregnant people, especially those who are most marginalized. Reproductive gerrymandering provides a means for theorizing the connections across domains involving partisan redistricting, reproductive governance in the form of anti‐abortion legislation, and the structural violence experienced by pregnant people seeking abortion.